If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 2y) = (2x + y) Remove parenthesis around (2x + 2y) 2x + 2y = (2x + y) Remove parenthesis around (2x + y) 2x + 2y = 2x + y Add '-2x' to each side of the equation. 2x + -2x + 2y = 2x + -2x + y Combine like terms: 2x + -2x = 0 0 + 2y = 2x + -2x + y 2y = 2x + -2x + y Combine like terms: 2x + -2x = 0 2y = 0 + y 2y = y Solving 2y = y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 2y + -1y = y + -1y Combine like terms: 2y + -1y = 1y 1y = y + -1y Combine like terms: y + -1y = 0 1y = 0 Divide each side by '1'. y = 0 Simplifying y = 0
| -6(-4x+3)=6(-4x-3) | | y^2+.4y-.05=0 | | x-(x-7/5)=3(x-34) | | 2/x-1=4/x^2-1 | | 2x+25=17 | | 5x+5=3x-7+3x | | 9+5b=-2(1-8b) | | 2w+3-5w=9 | | 4x+3+6x=73 | | -3/4-3/8m | | 4(3*2x)=3(2x+4x) | | 9(2x+6)+2x=134 | | 4s^2-144= | | X-7=3z | | 9(2x+6)+2x= | | C=x^2+5x+65 | | 0=x^2+50x+500 | | 6(5k-8)-20=11(2k-3)-3 | | 25x+17=2 | | 9+5b=-2(-8b) | | 10/4=15/x | | F(-3)=2x^2-7x+1 | | 3(y-2)-2(5y-1)=10 | | 2n-n=6*4 | | 3x^2-x-10=46 | | 6x+8+x=71 | | (2-3y)5+(8-y)*(-4)=0 | | 18-6c=-6 | | 7x+12=4x-6 | | -6xt-7=17 | | 41=4x+x+1 | | h^3=4 |